Response of non-chemical approaches of weed management in potato (Solanum tuberosum) crop under organic cultivation mode - GUPTA, VARSHA; SASODE, DEEP SINGH; JOSHI, EKTA; SINGH, Y K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during 2016-17 and 2017-18 at Gwalior, Madhya Pradesh, to study the effect of integrated weed management on weed species, yield and economics of potato (Solanum tuberosum L.) grown under chemical and non-chemical approaches of weed management. The treatments were white plastic mulch, black plastic mulch, straw mulching 5 t/ha (5 DAP), hand weeding (20 DAP) + straw mulching (25 DAP), two hand weedings (20 and 40 DAP), hand hoeing (20 DAP), hand hoeing (20 DAP) + hand weeding (40 DAP), metribuzin 500g/ha alone, metribuzin 500g/ha followed by hand weeding (40 DAP) and weedy check. Based on results, twice hand weeding deceased the weed density up to 86%, however one hand weeding with straw mulching 75%. At harvest, weed biomass under white and black plastic mulch compared to the weed infested treatment had highest around 46% in both but the lowest was observed where twice hand weeding was applied (19.20%) compared to weedy check. It can be concluded that twice hand weeding (20 and 40 DAP) resulted in better control of weeds with 78% WCE and maximum tuber yield (27.32 t/ha) followed by one hand weeding (20 DAP) + straw mulching (25 DAP) with 76% WCE and tuber yield 25.39 t/ha.